Assessment Of Machinery Of Agricultural Farms In Middle Pomerania (Research Bulletins of the Faculty of Economic Sciences, 2017)
The purpose of the present article is an assessment of the estate of agricultural farms in Middle Pomerania. An assessment was performed of the quantity of the means of transport, agricultural machines and machinery that are possessed by agricultural farms (based on data from the Central Statistical Office: National Agricultural Census). The spatial scope of the study covers Middle Pomerania and the whole of Poland. It is evident based on the research conducted that agricultural farms in Middle Pomerania are better equipped with means of transport, agricultural machines and machinery than the total of entities in Poland.
Keywords: estate; farms; Middle Pomerania